Evaluation of the functional egg supplement program for pregnant women with chronic energy deficiency - Sugiyanto, Nida Alhusna; Arjuna, Tony; Lazuardi, Lutfan (BKM Public Health and Community Medicine, 2022)
Purpose: This study aims to determine the effect of functional egg administration on changes in nutritional status, protein intake, and babies born. Methods: A study analytical with a cross-sectional design that was seen retrospectively. In-depth interviews were conducted with key informants and supporters to support research data. Results: Analysis found that consumption of functional eggs was not statistically related to nutritional status, weight, and length of the child's body but was descriptively related. Functional egg consumption is associated with increased energy and protein intake with p values ​​0.005 and 0.011 (p <0.05). There was an increase in body weight, MUAC, and nutritional status of chronic energy deficiency (CED) pregnant women becoming NON-CED, thereby reducing the birth of LBW and LBL. Conclusions: Functional eggs are not used as additional food; they become the mother's central protein intake. There is a need to increase commitment among organizers, implementers, and targets in implementing programs to break the stunting chain.